Rancang Bangun Trainer Pembangkit Lsitrik Tenaga Surya Dengan Metoda Off Grid dan On Grid Sebagai Media Perkuliahan Sistem Pembangkit - Asrul, Junaidi; -, Firmansyah; Hendri, Zulka; Putri, Dinda Desti (Jurnal Ilmiah Poli Rekayasa, 2023)
The DIV study program is a new study program so there are several courses that require practical equipment that supports the achievement of good learning of power plant systems, the current condition of practical equipment is still lacking and there are some that do not meet practical needs, so this research will create a power plant trainer tool Solar (PLTS) which functions as a learning medium in the integrated generator laboratory in the Electrical Installation Engineering Technology DIV study program. The aim of this research is to improve students' understanding of Solar Cell Power Plants, both installation methods and the working principles of supporting components both with On Grid systems and Off Grid systems. In making this trainer, it was carried out by assembling and making a trainer stand with a welding system and the mid-trainel was made using acrylic to make it easier to assemble the main components of the PLTS system. With this trainer tool, it will be very easy for students to design PLTS systems that will be used according to the energy needs used by customers. so that the installation of PLTS is in accordance with the required requirements, and also with this tool it is able to produce students' skills in assembling and installing PLTS correctly, both with On Grid Systems and Off Grid Systems, and students are able to optimize the placement of the installation position on the Solar Panel Module so that they are able to optimize the lighting received by the solar panels is good.